RNA-Seq analysis reveals critical transcriptome changes caused by sodium butyrate in DN mouse models. Issue 4 (30th April 2021) - Yang, Hansen; Zhang, Zheng; Peng, Rui; Zhang, Luyu; Liu, Handeng; Wang, Xinyi; Tian, Yiting; Sun, Yan
Abstract: Diabetic nephropathy (DN)—a common complication of diabetes—is the primary cause of end-stage renal disease. Sodium butyrate (NaB) is a short-chain fatty acid (SCFA) that is a metabolic product of intestinal bacterium, and its protective effect on the kidney has been reported in cases of DN. However, its underlying mechanism remains unclear. The aim of the present study was to investigate the effect of NaB on globe transcriptome changes in DN. In our study, 8-week-old male db/db mice suffering from DN were randomly divided into two groups: the DN+NaB group (DN mice treated with NaB, 5 g/kg/day) and the DN group (DN mice treated with saline). Further, normal db/m mice were used as the normal control (NC) group. The blood glucose, body weight, urinary microalbumin and urinary creatinine of mice were measured for all three groups. Whole-transcriptome analysis was performed by RNA sequencing (RNA-Seq) to evaluate the profiling of long non-coding RNAs (lncRNAs) and messenger RNAs (mRNAs). Bioinformatics analysis was performed to predict the potential NaB-related lncRNAs and genes in DN. The expressions of lncRNAs and mRNAs were tested using the quantitative real-time polymerase chain reactions (qRT-PCRs) in renal tissues and mesangial cells treated with NaB. The results of the present study demonstrated that NaB ameliorated renal dysfunction in DN mice. Moreover, RNA-Seq results identified that some lncRNAs and mRNAs were reversely changed in the DN+NaB group in comparison to those in the DN group. Additionally, the integrated co-expression networks of NaB-related lncRNAs revealed that these lncRNAs interacted with 155 key mRNAs. Furthermore, the co-expression network of inflammation-related lncRNAs and mRNAs demonstrated that those reversed lncRNAs and mRNAs also play essential roles in the inflammatory response. In summary, the present study suggests that NaB ameliorates diabetes-induced renal dysfunction and regulates transcriptome changes in DN.